Stepping out of line : becoming and being feminist - Hercus, Cheryl, 1954- (Perspectives on gender (New York, N.Y.), 2005)
What does it mean to be a feminist today? Why do some women become feminists and others do not? Stepping Out of Line offers an insightful account of the struggle of becoming and being a feminist.